Strategies for enhanced bioavailability of oxime reactivators in the central nervous system - Prchalova, Eliska; Kohoutova, Zuzana; Knittelova, Karolina; Malinak, David; Musilek, Kamil (Archives of toxicology, 2023)
Oxime reactivators of acetylcholinesterase are commonly used to treat highly toxic organophosphate poisoning. They are effective nucleophiles that can restore the catalytic activity of acetylcholinesterase; however, their main limitation is the difficulty in crossing the blood-brain barrier (BBB) because of their strongly hydrophilic nature. Various approaches to overcome this limitation and enhance the bioavailability of oxime reactivators in the CNS have been evaluated; these include structural modifications, conjugation with molecules that have transporters in the BBB, bypassing the BBB through intranasal delivery, and inhibition of BBB efflux transporters. A promising approach is the use of nanoparticles (NPs) as the delivery systems. Studies using mesoporous silica nanomaterials, poly (L-lysine)-graft-poly(ethylene oxide) NPs, metallic organic frameworks, poly(lactic-co-glycolic acid) NPs, human serum albumin NPs, liposomes, solid lipid NPs, and cucurbiturils, have shown promising results. Some NPs are considered as nanoreactors for organophosphate detoxification; these combine bioscavengers with encapsulated oximes. This study provides an overview and critical discussion of the strategies used to enhance the bioavailability of oxime reactivators in the central nervous system.
Keywords: Biological Transport; biologický transport; centrální nervový systém; Central Nervous System; Acetylcholinesterase; Humans; hematoencefalická bariéra; lidé; Blood-Brain Barrier; acetylcholinesterasa; biologická dostupnost; Biological Availability